The Effect of Health Information Technology Assets on the Sustainability of Health Management Information Systems Usage Moderated by Strategy in Kendari City - Jumakil, Jumakil; Syaifuddin, Dedy Takdir; Jaya, Muhammad Golok; Yuniar, Nani (YCAB Publisher, 2024)
Background:Health policies in Indonesia facilitate public access to healthcare information in efforts to improve public health. These policies rely on the support of electronic healthcare information systems to provide health data and information. However, the usage of these systems faces various challenges that affect their sustainability. Objective:To determine the effect of healthcare information technology assets on the sustainability of healthcare management information systems and the role of healthcare information technology strategies as a moderating variable. Methods:This is a quantitative and explanatory research study. The sample consisted of 350 respondents, with a significance level of 0.05. Latent variables included the sustainability of healthcare management information system usage, healthcare information technology assets, and information system strategies, which also served as an intervening variable. Results:The direct effect test yielded a p-value of 0.000 (<0.05), leading to the rejection of the null hypothesis. Thus, healthcare information technology assets and healthcare information technology strategies have a positive and significant effect on the sustainability of healthcare management information system usage. The indirect effect test yielded a p-value of 0.003 (<0.05), also leading to the rejection of the null hypothesis. These results indicate that the healthcare information technology strategies variable moderates the effect of healthcare information technology assets on the sustainability of healthcare management information system usage. Conclusion:Healthcare information technology strategies strengthen the effect of healthcare information technology assets on the sustainability of healthcare management information system usage. Keywords:Health Policy; Health Information Systems; Information Technology; Indonesia